EFEKTIVITAS PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Ikhwan Malkanov; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Implementation of Self-Help Housing Stimulant Assistance, abbreviated as BSPS, is government assistance for low-income people to encourage and increase self-sufficiency in improving the quality of houses and the construction of new houses along with infrastructure, facilities and public utilities. In Kuantan Singingi Regency, it has received Self-Help Housing Stimulant Assistance from 2017 to 2021. In 2019 there are 15 Districts and of the total 1,192 housing units that are not suitable for habitation, the largest number are in Singingi District, namely 256 houses unfit for habitation. In Singingi District, there are 8 villages that received BSPS assistance, 2 of the 8 villages that received assistance were Kebun Lado Village and Air Emas Village. In 2019, Kebun Lado Village received 22 units and Air Emas received 22 units. BSPS assistance is in the form of money. The purpose of this study was to determine the effectiveness of the BSPS Program in Singingi District and to analyze the inhibiting factors in the effectiveness of the BSPS Program in Singingi District. This research uses recording techniques and note taking techniques with this type of qualitative research using a phenomenological approach. The collection of data obtained both primary data and secondary data were collected through interviews, observation and documentation then based on research problems. The results of this study indicate that the effectiveness of the BSPS Program in Singingi District is not optimal, this is due to several inhibiting factors, namely from the researcher's initial observations there are phenomena in the implementation of this government program, namely, supervision of the implementation of development due to supervision from the related Service, as well supervise the implementation of the BSPS program and identify and anticipate problems that occur in the field. On the other hand, in the field, such as under Swadaya from the beneficiaries, the supply of materials from the material distributor shop is not in accordance with the agreement with the beneficiaries, the part of cooperation between members and groups. Keywords:Effectiveness, BSPS Program, Kebun Lado Village and Air Emas